2010
DOI: 10.1016/j.maturitas.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine physiology of female reproductive aging: An update

Abstract: The transition into menopause is a complex process that affects fertility and increases the risk for a number of health problems in aging women that include, but are not limited to osteoporosis, heart disease, diabetes mellitus and cognitive dysfunction. Improved nutrition and enhanced access to medical care have increased the average lifespan for women in developed countries, and many will spend more than one third of their life in a post-menopausal state. Epidemiological studies indicate that a delayed natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…The answer to this stems from differences in the mechanisms and the trajectory of spontaneous, transitional reproductive senescence in the two species. In women, the depletion of the ovarian follicles ultimately induces reproductive senescence (Neal-Perry et al, 2010). Conversely, in female rodents, the ovaries remain capable of reproduction given that transfer of an ovary from an aged donor rat to a young female recipient can still result in the support of normal cyclicity and the maintenance of viable pregnancies (Peng and Huang, 1972).…”
Section: Use Of Rodent Models To Assess Estrogenic Actions In the mentioning
confidence: 99%
See 1 more Smart Citation
“…The answer to this stems from differences in the mechanisms and the trajectory of spontaneous, transitional reproductive senescence in the two species. In women, the depletion of the ovarian follicles ultimately induces reproductive senescence (Neal-Perry et al, 2010). Conversely, in female rodents, the ovaries remain capable of reproduction given that transfer of an ovary from an aged donor rat to a young female recipient can still result in the support of normal cyclicity and the maintenance of viable pregnancies (Peng and Huang, 1972).…”
Section: Use Of Rodent Models To Assess Estrogenic Actions In the mentioning
confidence: 99%
“…Instead, the proposed mechanism of female rodent reproductive senescence is dysregulation of the hypothalamic-pituitary-gonadal axis to respond to 17βE2 positive feedback. Indeed, Selmar Aschheim's 1964 seminal findings revealed that transplant of a young adult ovary into an aged rats failed to restore cyclicity (Neal-Perry et al, 2010). Similarly, transplant of hypothalamic nuclei from an aged rat into a young recipient disrupted normal cyclicity in these younger animals (Peng and Huang, 1972).…”
Section: Use Of Rodent Models To Assess Estrogenic Actions In the mentioning
confidence: 99%
“…Considering the numerous similarities of the endocrine milieu in middle-aged female rats and in menopausal women [20], we have used an ovary-intact middle-aged rat model. Furthermore, the existing literature data mostly elaborate the effects of phytoestrogens, as nutritional supplements or alternative therapy, in ovariectomized (ovx) rats, so the present study attempts to be a step forward.…”
Section: Introductionmentioning
confidence: 99%
“…Although accelerated ovarian follicle depletion marks the transition to menopause, the process leading up to reproductive senescence is complex, beginning before birth and continuing for decades [3]. In mammals, the finite population of oocytes found in the reproductively mature ovary is established during embryogenesis when the primordial germ cells undergo mitotic division and form oogonia.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as smoking and diet [7], and a definite genetic component [8,9] can also influence the age at menopause in humans. Understanding how these many diverse mechanisms affect ovarian function and aging may reveal strategies to delay menopause or alleviate the health challenges often presenting in postmenopausal women [3].…”
Section: Introductionmentioning
confidence: 99%